1999
DOI: 10.1046/j.1440-1622.1999.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Control Study on the Effect of Branched‐chain Amino Acids in Patients With Liver Resection for Hepatocellular Carcinoma

Abstract: Aminoleban EN is safe to administer and does not have significant adverse effects. It contributes to a shorter hospital stay and quicker improvement of liver function in the early postoperative period. These beneficial results require only a 12-week period of administration of BCAA after operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 8 publications
2
73
0
2
Order By: Relevance
“…In contrast, long lasting effects of BCAA supplementation were reported in patients with a metabolic or nutritional deficiency like in septic or cancer patients. In these patient groups BCAA supplementation was reported to result in positive effects on albumin status, quality of life and overall survival (Jimenez Jimenez et al, 1991;Garcia-de-Lorenzo et al, 1997;Surgery, 1997;Meng et al, 1999;Poon et al, 2004). Moreover, it has been reported that protein synthesis can only be stimulated in the presence of a high supply of balanced amounts of essential amino acids (Rooyackers and Nair, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, long lasting effects of BCAA supplementation were reported in patients with a metabolic or nutritional deficiency like in septic or cancer patients. In these patient groups BCAA supplementation was reported to result in positive effects on albumin status, quality of life and overall survival (Jimenez Jimenez et al, 1991;Garcia-de-Lorenzo et al, 1997;Surgery, 1997;Meng et al, 1999;Poon et al, 2004). Moreover, it has been reported that protein synthesis can only be stimulated in the presence of a high supply of balanced amounts of essential amino acids (Rooyackers and Nair, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…There are two clinical trials in cancer patients that studied oral BCAA supplementation after surgical removal of the tumour. These studies reported a shorter hospital stay, a better performance status at 3 months and an increased body mass at 1 year following surgery (Surgery, 1997;Meng et al, 1999). BCAAs have also been supplemented in the presence of the tumour: patients undergoing chemotherapy received oral BCAA supplementation up to 1 year after the start of chemotherapy, resulting in a lower overall morbidity, an improved nutritional status and a better quality of life (Poon et al, 2004).…”
mentioning
confidence: 99%
“…Furthermore, another randomized trial showed that oral BCAA supplementation after hepatectomy for HCC significantly reduced the 30 month recurrence of HCC (28.5% vs 55.7%, P = 0.044) [75] . Perioperative BCAA treatment in patients undergoing hepatectomy was also shown to contribute to shorter hospital stay and quicker improvement of liver function during the early postoperative period [76] and to improve postoperative quality of life by restoring and maintaining nutritional status and whole-body kinetics [77] . The effect of BCAAs on HCC recurrence after radiofrequency ablation (RFA) remains unclear.…”
Section: Bcaas For Liver Cirrhosismentioning
confidence: 99%
“…One trial of parenteral nutrition 53 and five of supplements [54][55][56][57][58] included patients with hepatocellular carcinoma. The current data do not compellingly justify the routine use of parenteral nutrition, enteral nutrition, or oral nutritional supplements in these patients.…”
Section: Nutrition Management In Terminal Stage Hepatocellular Carcinomamentioning
confidence: 99%